Improved formulation for the geometric characteristics of the scour hole and deposition mound caused by a rotating propeller jet on a mobile bed. (1st January 2023) - Curulli, Giuseppe; Penna, Nadia; Gaudio, Roberto
Abstract: The densimetric Froude number, F 0, which depends on the propeller rotational speed, n, and on the median diameter of bed sediments, d 50, is the main parameter considered by researchers for analysing the propeller-induced scouring process. Common literature equations for evaluating the three-dimensional (3D) geometric characteristics of the scour hole and deposition mound are functions of F 0 . In this paper, the agreements among the data and these literature equations are critically discussed, demonstrating that the use of other two dimensionless parameters (the propeller Froude number, F 0 p, and d 50 / D p where D p is the propeller diameter), which are separately dependent on n and d 50, returns more satisfying results than using F 0 solely. Also, the influence of the water depth, h, on the scour hole and the deposition mound is here analysed. Researchers commonly neglected the effects of h, because the ratio between it and D p was large enough. This is reasonably true when h / D p is considerably high, but no clear cut-off value was found in the literature. For the first time, by investigating a larger range of h, the present study underlines that the effects of h on the scour hole and the deposition mound are negligible for h / D p ≥ 2.44. Highlights: The effects of the water depth on the scour hole and the deposition mound induced by a rotating propeller are analysed. The effects of the submergence depth and of the rotational speed on the equilibrium bed profiles are investigated. An improved formulation for the geometric characteristics of the scour hole and of the deposition mound is presented. The total eroded area induced by a propeller jet flow is measured for the first time.